Hydrogen storage in TiVCrMo and TiZrNbHf multiprinciple-element alloys and their catalytic effect upon hydrogen storage in Mg. (April 2022) - Cermak, Jiri; Kral, Lubomir; Roupcova, Pavla
Abstract: Hydrogen storage performance of nearly equimolar alloys TiVCrMo and TiZrNbH (HEA's) was studied. The alloys were prepared by repeated arc-melting in the form of single-phase alloys and as their multi-phase analogues prepared either by high-energy ball milling (HEBM) of the arc-melted ingots or by HEBM of pure elements. Besides these four-component experimental materials, also their mixtures with Mg were investigated that were prepared by HEBM with Mg (composition in both cases was Mg – 10 wt % HEA). Hydrogen sorption experiments were carried out in temperature interval between 240 °C and 380 °C under hydrogen-gas pressure up to 50 bars. Kinetic curves, temperature-programmed desorption spectra and concentration-pressure isotherms were measured. It was found that activation energy of hydrogen desorption, | E a |, for materials with Mg was significantly decreased compared to pure Mg. Hydride formation enthalpy, Δ H, observed for all the materials under study was about the same as that for pure MgH2 . Hydrogen absorption capacity in pure four-component HEA's was negligible; only hydrogen surface adsorption was detected. The capacity of mixtures of HEA's with Mg was between 3.5 and 6 wt % H2 .